1991
DOI: 10.1176/ajp.148.10.1371
|View full text |Cite
|
Sign up to set email alerts
|

The comorbidity of borderline personality disorder and other DSM-III-R axis II personality disorders

Abstract: Borderline personality disorder appears to constitute a broad, heterogeneous category with unclear boundaries that embraces a general personality disorder concept. Both further refinement of the borderline personality disorder construct and investigation into alternative models to the DSM-III-R axis II classification system are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(2 citation statements)
references
References 47 publications
0
1
1
Order By: Relevance
“…This result is also consistent with the view that narcissistic personality is the male variant of BPD (Gunderson, 1988). In our study we found that the rate of co-occurring antisocial personality disorder (APD) in BPD was only 1.1%, which is lower than in several previous studies (McGlashan et al, 2000; Nurnberg et al, 1991; Stuart et al, 1998; Zanarini et al, 1987). This finding may be due to our sample characteristics.…”
Section: Discussioncontrasting
confidence: 73%
“…This result is also consistent with the view that narcissistic personality is the male variant of BPD (Gunderson, 1988). In our study we found that the rate of co-occurring antisocial personality disorder (APD) in BPD was only 1.1%, which is lower than in several previous studies (McGlashan et al, 2000; Nurnberg et al, 1991; Stuart et al, 1998; Zanarini et al, 1987). This finding may be due to our sample characteristics.…”
Section: Discussioncontrasting
confidence: 73%
“…While the utility of adjustment factors in enhancing clinical accuracy has substantial support in the psychometric literature (see Choca, 2004), their use contributes further complexity to the MACI’s already complex scoring system. Thus, although clinically useful, the uncommon scoring conventions used by the MACI and other Millon instruments may also serve to confound scale interpretation and negatively affect content validity (see Choca, 2004; Nurnberg, Hurt, Feldman, & Suh, 1987; Nurnberg et al, 1991; Rossi, Elklit, & Simonsen, 2010).…”
mentioning
confidence: 99%